DIGITAL STORYTELLING AS A POST–LISTENING ACTIVITY IN TEACHING NARRATIVE TEXT TO THE 5 GRADE STUDENTS: THE IMPLEMENTATION AND STUDENTS’ RESPONSES - Rizky Sulvika Puspa Rinda; Dyah Palupi Saraswati (English Department of Faculty of Tarbiyah and Teacher Training, 2021)
Digital Storytelling is a modern form of the storytelling art. The implementation of digital storytelling is expected to provide an alternative classroom activity in teaching listening and help the students in understanding a text as well as learning the value, particularly in narrative text. This study presented the description of the implementation of digital storytelling as a post–listening activity to teach narrative text to the fifth grade students. The data of the study gathered from the result of observation that was obtained through observation sheet and field notes, and interview in order to find out the students’ responses toward the activity. The data were collected by observing the teacher’s and students’ activities during the teaching and learning processes in the classroom, and interviewing the students’ opinions and teacher’s perception after implementing digital storytelling. The result of the observation showed that the fifth grade students were able to create their digital storytelling, even though one step was omitted and the other two steps were conducted at the same time. Meanwhile, from the result of interview, it was found that the students enjoyed in joining the lesson. Thus, the implementation of digital storytelling had improved the students’ mastery in understanding narrative text.